Launch of the Colombo Center of Excellence GHRU - Chambers, John; Wijeyaratne, Chandrika (Faculty of Medicine, University of Colombo, 2020)
The National Institute of Health Research-Global Health Research Unit (NIHR-GHRU) Centre of Excellence for Non-communicable Diseases (NCD) in Sri Lanka is a joint venture between University of Colombo and University of Kelaniya, and Imperial College London. The centre is funded by the National Institute of Health Research, United Kingdom. The centre will establish and maintain a strong collaboration with the Ministry of Health, Sri Lanka. The Colombo Center will be located at the ClinMARC building of the University of Colombo in the National Hospital of Sri Lanka. The vision: Reduce the burden of NCDs in Sri Lanka The mission and activities: The centre will engage in NCD and risk factor surveillance, capacity building especially by promoting young researchers on NCD related research, training, public empowerment and advocacy to reduce the impact of NCDs on the morbidity and mortality of the Sri Lankan population and thereby on the economic and social development of Sri Lanka